The deregulation of arachidonic acid metabolism in ovarian cancer - Xia, Qiuyi; Gao, Wen; Yang, Jintao; Xing, Zhifang; Ji, Zhaodong (Frontiers in Oncology, 2024)
Arachidonic acid (AA) is a crucial polyunsaturated fatty acid in the human body, metabolized through the pathways of COX, LOX, and cytochrome P450 oxidase to generate various metabolites. Recent studies have indicated that AA and its metabolites play significant regulatory roles in the onset and progression of ovarian cancer. This article examines the recent research advancements on the correlation between AA metabolites and ovarian cancer, both domestically and internationally, suggesting their potential use as biological markers for early diagnosis, targeted therapy, and prognosis monitoring.